The Implementation of English Medium Instruction (EMI) at the Public Secondary Schools in South Sulawesi Indonesia: Students’ Voices - Baa, Sultan; Maghfirah, Nurul; Borland, Helen (Universitas Negeri Makassar, 2023)
This article presents analysis and discussion of research data focusing on the students’ attitudes and perceptions of EMI program implementation strategies in the secondary schools level in South Sulawesi Province. Three Public International Standard Schools that run EMI and non-EMI Programs were selected as sample of the study. The data has been drawn from student questionnaire responses and student group interviews. Seventy seven (77) EMI students and 84 non-EMI students completed the questionnaire. Eight students from each school were selected as focus group interview participants. The data from questionnaire was analysed using SPSS Program, and the data from focus group interview was analysed using NVivo software. The study found that the Chi-square test result suggests that in these three schools, EMI and non-EMI programs have significant differences in their preferences (p=0.000). EMI students preferred the EMI program and non-EMI students preferred non-EMI programs. Futhermore, the students said they experienced difficulties studied in the program. Despite the fact that students experienced difficulties in coping with the new learning situation in the EMI program, the majority felt satisfied with the program because they realised there were some benefits. The students interview responses also highlighted three factors detracting from EMI program implementation: lack of teachers’ language support; lack of English environment in the school; and bilingual learning materials. Detailed findings will be presented and their implications discussed.